IMPLEMENTATION OF GALLERY WALK IN COOPERATIVE LEARNING TO IMPROVE HIGH SCHOOL STUDENTS' MOTIVATION AND LEARNING OUTCOMES - Aulya Adibba; Farid Gunadi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
Abstract High school students often experience low motivation and suboptimal achievement in mathematics learning, particularly in the topic of sequences and series. This condition underscores the need for instructional strategies that can enhance students engagement and conceptual understanding. This study aims to examine the effect of Gallery Walk based cooperative learning on students learning motivation and achievement in mathematics among Grade X students at SMAN 1 Indramayu. The research employed Classroom Action Research, with students of class X serving as the research subjects. Data were collected through motivation questionnaires, learning achievement tests, and classroom observations, and were analyzed using descriptive qualitative and quantitative methods. The results indicate an improvement in students learning motivation, as reflected in increased participation, enthusiasm, and collaboration, as well as a significant improvement in learning outcomes from Cycle I to Cycle II. These findings demonstrate that Gallery Walk based cooperative learning is an effective pedagogical approach for fostering active learning environments and improving students understanding of mathematical concepts, thereby contributing to the enhancement of mathematics instruction at the secondary school level. Keywords: Cooperative Learning, Gallery Walk, Learning Motivation, Learning Outcomes, Sequences and Series.